Guidance for Endoscopic Procedures in Patients Taking Novel Oral Anticoagulants - Kyoung Oh Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Anticoagulant agents are used to reduce the risk of thromboembolic complications in patients with atrial fibrillation or deep vein thrombosis. Several new generation of oral anticoagulants have been approved. These novel oral anticoagulants (NOACs) include direct thrombin inhibitors, dabigatra etexilate, and the direct factor Xa inhibitors, rivaroxaban, apixaban and edoxaban. This review evaluates NOACs-related gastrointestinal bleeding and summarizes the ideal management strategies based on the guideline suggested by American Society for Gastrointestinal Endoscopy.